EFEKTIVITAS LATIHAN PANGGUL MENCEGAH ATROPI OTOT PADA PASIEN STROKE NON HEMORAGIK - Ikaningtyas, Nurlia (Jurnal Kesehatan, 2017)
ABSTRACT Background: Stroke is the leading cause of death in Indonesia. According to Data Center and Information Ministry of the Republic of Indonesia in 2013, it was estimated 1,236,825 people died because of stroke. Stroke patients have many complications one of them is muscle atrophy. Post-stroke muscle atrophy leads to functional incapacity which decreases the quality of patients’ life. Appropriate action will prevent muscle atrophy. Objective: This study aims to determine whether there is a difference between patients who were given pelvic exercises in intervention group and Brief Repetitive Isometric Maximum Exercise (BRIME) in control group. Method: This research was a quasi post-test experimental non-equivalent control group study design. The sample was 30 respondents with 15 respodents in intervention group and 15 respondents in control group. It applied purposive sampling technique and independent t-test with ?: 0.05. Result : The result shows no significant difference between the size of the circumference femuralis in control group and in intervention group with P value: 0.451. Conclusion: Pelvic exercises and BRIME can prevent muscle atrophy. However, the result shows that pelvic exercises increase the size of the circumference of muscle femuralis while BRIME decreases it. Suggestion: Other researchers who want to do the same research are suggested to pay attention to the confounding factors, such as nutritional status, extensive infarction, and increase the time allocation of the study.